Development Of Scientific And Technical Terms In English And Uzbek (Eurasian Journal of Learning and Academic Teaching, 2026)
The development of scientific and technical terminology constitutes a fundamental aspect of linguistic modernization, knowledge production, and cross-cultural communication. English, as the dominant language of global science and technology, demonstrates extensive lexical productivity through derivation, compounding, borrowing, and semantic extension. Uzbek, as a dynamically developing language in scientific domains, has expanded its terminological system through affixation, compounding, calquing, and systematic borrowing from Persian, Arabic, Russian, and increasingly English. This study investigates the mechanisms of term formation in English and Uzbek from a comparative and translational perspective. Drawing upon terminology theory and translation studies, the research analyzes word-formation processes, semantic adaptation, and strategies of equivalence in medicine, engineering, and information technology. The findings reveal both structural divergences and functional convergences in terminological development. While English favors morphological innovation and hybrid classical formations, Uzbek demonstrates structured adaptation through affixation and calquing to maintain semantic transparency. The study contributes to terminology theory, comparative linguistics, and translation practice by emphasizing the importance of systematic term development for scientific literacy, language planning, and international knowledge exchange.